Action presidents. #2, Abraham Lincoln! - Van Lente, Fred (Van Lente, Fred. Action presidents, 2018)
Presents a humorous graphic novel offering true stories about Abraham Lincoln, such as the fact that he was the first president to pardon a White House turkey on Thanksgiving.